Narrative Review: Terapi Kortikosteroid Pada Pasien COVID-19 dengan Komorbiditas Diabetes Melitus - Novia Ariani Dewi; Tri Murti Andayani; Ika Trisnawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
COVID-19 is a respiratory disease caused by SARS-CoV-2, a corona virus that was discovered at the end of 2019. Diabetes mellitus (DM) is the second highest comorbidities in Indonesia of COVID-19 patients. One of the treatments for COVID-19 patients is corticosteroids. Commonly used corticosteroids are dexamethasone, methylprednisolone, and hydrocortisone. This study aims to determine the effect of corticosteroid therapy in COVID-19 patients with DM comorbidities so that it can be a source of information and a reference in the management of therapy in patients. This research is a narrative review using literature from the science databases Cochrane, PubMed and Science Direct. Literature search used the keywords COVID-19, diabetes, and corticosteroids. The results of the literature screening obtained 16 study articles that met the inclusion criteria. The conclusion of this narrative review study is that the recommended corticosteroid therapy for COVID-19 patients is dexamethasone. Administering corticosteroids to COVID-19 patients with comorbid DM can increase the incidence of hyperglycemia, especially at high doses and in the long term, thereby worsening the patient's prognosis, causing new onset diabetes, and increasing the need for insulin doses.